2017
DOI: 10.1016/j.quageo.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance dating of optically bleached quartz grains from the Middle Palaeolithic site of Cuesta de la Bajada (Spain) using the multiple centres approach

Abstract: Electron spin resonance (ESR) dating of optically bleached quartz grains was performed on three sediment samples collected from the Middle Palaeolithic site of Cuesta de la Bajada (Spain). A standard multiple grain and multiple aliquot additive dose procedure was employed, and both the Al and Ti centres were measured as part of the multiple centres approach. ESR age estimates obtained for the three samples indicate that the Al centre provides a maximum possible chronology; use of the Ti centres show that the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
78
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 56 publications
(89 reference statements)
11
78
0
Order By: Relevance
“…In contrast, the Ti-H centre provides age estimates that are in agreement with the ESR/U-series results. This demonstrates the great potential of this centre to date late Middle Pleistocene deposits, which is consistent with previous observations by Duval et al (2017). A multiple centre approach seems therefore indispensable when dating this type of fluvio-estuarine sediment, even when the sedimentological characteristics of the sediments seem initially quite suitable for an ESR study (as it was the case for the Tourville D1 and I units).…”
Section: Accepted Manuscriptsupporting
confidence: 86%
See 4 more Smart Citations
“…In contrast, the Ti-H centre provides age estimates that are in agreement with the ESR/U-series results. This demonstrates the great potential of this centre to date late Middle Pleistocene deposits, which is consistent with previous observations by Duval et al (2017). A multiple centre approach seems therefore indispensable when dating this type of fluvio-estuarine sediment, even when the sedimentological characteristics of the sediments seem initially quite suitable for an ESR study (as it was the case for the Tourville D1 and I units).…”
Section: Accepted Manuscriptsupporting
confidence: 86%
“…Previous cross-comparison studies showed good agreement with results derived from other numerical dating methods such as Luminescence, U-series and 40 Ar (e.g. Duval et al, 2017;Méndez-Quintas et al, 2018;Pereira et al, 2018). Unfortunately, given the very limited number of laboratories and researchers specialized in the ESR dating applications mentioned above, inter-laboratory comparison studies remain very rare.…”
Section: Accepted Manuscriptsupporting
confidence: 67%
See 3 more Smart Citations